Challenges in the adoption of hybrid cloud: an exploratory study using systematic literature review. Issue 5 (6th May 2016) - Khan, Siffat Ullah; Ullah, Naeem
Abstract : Cloud computing is a growing computing paradigm that provides Internet‐based computer services on‐demand basis. Adoption of cloud infrastructure promises enterprises numerous benefits. In particular, hybrid cloud, a combination of both public and private clouds, offers benefits of both the public and private clouds. The objective of this study is to identify the critical challenges, faced by client organisations in the adoption of hybrid cloud computing. The authors have reviewed the literature through systematic literature review (SLR) process. We have followed all the SLR steps by developing SLR protocol first which was then validated and implemented. We have identified a list of ten challenges, by extracting data from a sample of 120 papers, in the adoption of hybrid cloud. The identified challenges include three critical challenges such as: 'public cloud security concern', 'efficient management issue', and 'integration complexity'. We have further analysed the identified challenges with respect to time and study strategy. Clients should address all the identified challenges in general and the critical challenges in particular. Our next phase of the study is validation of the identified challenges through industry practitioners and to find solutions/practices for addressing these challenges, which will be published in future.